1988
DOI: 10.1016/0167-4889(88)90130-9
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil protein kinase C: calcium-induced changes in the solubility of the enzyme do not always correlate with enzymatic activity

Abstract: We hypothesized that calcium and 1,2-diacylglycerols stimulated human neutrophil (PMN) protein kinase C (EC 2.7.1.37) in a two-step mechanism. The proposed mechanism entails (1) increased insoluble protein kinase C activity and (2) endogenous protein phosphorylation, events which have not been biochemically dissociated. PMN which were treated with 100 nM ionomycin shifted protein kinase C activity from being mostly soluble to insoluble. Concentrations of ionomycin greater than 300 nM stimulated a doubling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although previous in vitro studies on neutrophil function from healthy control subjects has shown that paracetamol (even at toxic concentrations) does not affect chemotaxis or superoxide production [25][26][27], it is possible that an in vivo overdose could inhibit neutrophil function. Although previous in vitro studies on neutrophil function from healthy control subjects has shown that paracetamol (even at toxic concentrations) does not affect chemotaxis or superoxide production [25][26][27], it is possible that an in vivo overdose could inhibit neutrophil function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although previous in vitro studies on neutrophil function from healthy control subjects has shown that paracetamol (even at toxic concentrations) does not affect chemotaxis or superoxide production [25][26][27], it is possible that an in vivo overdose could inhibit neutrophil function. Although previous in vitro studies on neutrophil function from healthy control subjects has shown that paracetamol (even at toxic concentrations) does not affect chemotaxis or superoxide production [25][26][27], it is possible that an in vivo overdose could inhibit neutrophil function.…”
Section: Discussionmentioning
confidence: 94%
“…The cause of ALF in this series of patients was paracetamol overdose. Although previous in vitro studies on neutrophil function from healthy control subjects has shown that paracetamol (even at toxic concentrations) does not affect chemotaxis or superoxide production [25][26][27], it is possible that an in vivo overdose could inhibit neutrophil function. In this study, all patients assessed were receiving an infusion of N-acetylcysteine when the assays were performed.…”
Section: Discussionmentioning
confidence: 94%